Association of arterial stiffness with a prothrombotic state in uncomplicated nondiabetic hypertensive patients - Brosolo, Gabriele; Da Porto, Andrea; Bulfone, Luca; Vacca, Antonio; Bertin, Nicole; Vivarelli, Cinzia; Sechi, Leonardo A.; Catena, Cristiana (Frontiers in Cardiovascular Medicine, 2023)
Background and aims: Past studies reported a significant contribution of a prothrombotic state to the development and progression of target organ damage in hypertensive patients. Stiffening of arterial vessels is associated with aging and hypertension, and additional factors could contribute to this process. This study was designed to examine the relationships between arterial stiffening and the hemostatic and fibrinolytic system. Methods: In 128 middle-aged, nondiabetic, essential hypertensive patients without major cardiovascular and renal complications, we measured coagulation markers that express the spontaneous activation of the hemostatic and fibrinolytic system and assessed stiffness of the arterial tree by measurement of the carotid/femoral pulse wave velocity (cfPWV) and pulse wave analysis with calculation of the brachial augmentation index (AIx). Results: Levels of fibrinogen (FBG), D-dimer (D-d), and plasminogen activator-inhibitor 1 (PAI-1) were significantly higher in patients with PWV and AIx above the median of the distribution. FBG, D-d, and PAI-1 were significantly and directly related with both cfPWV and AIx, and multivariate regression analysis indicated that the relationships of D-d and PAI-1 with both cfPWV and AIx and of FBG with AIx, were independent of age, body mass index, severity and duration of hypertension, use of antihypertensive drugs, blood glucose, and plasma lipids. Conclusion: In middle-aged, uncomplicated, nondiabetic patients with essential hypertension, spontaneous activation of plasma hemostatic cascade and impaired fibrinolysis is significantly and independently associated with stiffening of the arterial tree.